A social network perspective on the interaction between policy bubbles - Moshe Maor (International Review of Public Policy)
Studies of policy bubbles have so far ignored the possibility that a policy bubble in a given policy domain or jurisdiction may constitute an information event for another policy bubble that has been inflated elsewhere. In addition, studies of policy diffusion have paid little attention to the transmission of imperfect and wrongful policy valuations through social networks. To bridge these gaps, this article develops a theoretical framework and methodological toolbox for explaining the potential impact of interbubble dynamics on the sustainment of policy bubbles. This is achieved by focusing on: (i) the diffusion of interbubble connectivity information through social networks characterized by varying levels of segregation; (ii) the perceptions of distorted or corrected information by individuals at the receiving end as being factual, thus requiring no gap-filling by policy actors, or as an opinion that therefore requires gap-filling; (iii) the derived consequence in terms of simple or complex contagion; and (iv) its impact on the sustainment of policy bubbles. The main contribution of the article lies in unpacking the potential causal mechanisms through which a policy bubble can be sustained, even if positive feedback processes and contagion in the jurisdiction within which it developed no longer bolster its support bases.